Some New Weighted Results for the Hardy Operator on Variable-Exponent λ-Central Morrey Space (European Journal of Pure and Applied Mathematics, 2025)
The main purpose of this study is to demonstrate that the fractional Hardy operators are bounded on the weighted variable central Morrey space. When the symbol functions belong to the λ-central BMO space with a variable exponent, the estimates for their commutators are similar.
Keywords: Fractional operators, Weighted Morrey space, Variable exponent, Integral operators.